Music with the brain in mind - Jensen, Eric, 1950-; Marbles: The Brain Store (San Diego, CA : The Brain Store, 2000)
... With sections devoted to theory, as well as practical strategies and applications for the classroom ... a primer on how the body hears music to music's impact on stress level, perceptual-motor skills, memory, and emotional intelligence ... Included are tips for choosing music and the various benefits of various music types-- compare back cover
-- Building a music foundation -- Making a case for music -- Music in action
Includes bibliographical references and index
Keywords: Music -- Physiological aspects; Music -- Psychological aspects; Music -- Instruction and study; Brain